A Novel NASICON‐Type Na4MnCr(PO4)3 Demonstrating the Energy Density Record of Phosphate Cathodes for Sodium‐Ion Batteries. Issue 11 (9th February 2020) - Zhang, Jian; Liu, Yongchang; Zhao, Xudong; He, Lunhua; Liu, Hui; Song, Yuzhu; Sun, Shengdong; Li, Qiang; Xing, Xianran; Chen, Jun
Abstract: Sodium‐ion batteries (SIBs) have attracted incremental attention as a promising candidate for grid‐scale energy‐storage applications. To meet practical requirements, searching for new cathode materials with high energy density is of great importance. Herein, a novel Na superionic conductor (NASICON)‐type Na4 MnCr(PO4 )3 is developed as a high‐energy cathode for SIBs. The Na4 MnCr(PO4 )3 nanoparticles homogeneously embedded in a carbon matrix can present an extraordinary reversible capacity of 160.5 mA h g −1 with three‐electron reaction at ≈3.53 V during the Na + extraction/insertion process, realizing an unprecedentedly high energy density of 566.5 Wh kg −1 in the phosphate cathodes for SIBs. It is intriguing to reveal the underlying mechanism of the unique Mn 2+ /Mn 3+, Mn 3+ /Mn 4+, and Cr 3+ /Cr 4+ redox couples via X‐ray absorption near‐edge structure spectroscopy. The whole electrochemical reaction undergoes highly reversible single‐phase and biphasic transitions with a moderate volume change of 7.7% through in situ X‐ray diffraction and ex situ high‐energy synchrotron X‐ray diffraction. Combining density functional theory (DFT) calculations with the galvanostatic intermittent titration technique, the superior performance is ascribed to the low ionic‐migration energy barrier and desirable Na‐ion diffusion kinetics. The present work can offer a new insight into the design of multielectron‐reaction cathode materials for SIBs. Abstract : A novel NASICON‐type Na4 MnCr(PO4 )3 cathode presents an unusual reversible Mn 2+ /Mn 3+, Mn 3+ /Mn 4+, and Cr 3+ /Cr 4+ three‐electron reaction with a moderate volume change during Na + extraction/insertion, enabling an unprecedentedly high energy density in polyanionic cathode materials for sodium‐ion batteries.